2018
DOI: 10.1039/c7se00519a
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic relationship between the three-dimensional nanostructure and electrochemical performance in biocarbon supercapacitor electrode materials

Abstract: Different characterization techniques were used to analyse the chemically activated carbons in (i) one dimensional analysis including MIP and BET, (ii) two dimensions including SEM and TEM and (iii) three dimensional X-ray CT. This structure has been directly linked to the electrochemical performance of supercapacitors for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 49 publications
(66 reference statements)
2
25
0
Order By: Relevance
“…[2,17,18] Sevilla et al [13] reported N-doped carbons with surface areas of~2400 m 2 /g from hydrothermal carbonization and activation using microalgae as biomass precursor. The use of biomass-derived cellulose for producing porous carbons as electrodes for supercapacitor has also been reported giving excellent performance [19] and the incorporation of certain types heteroatoms into frameworks has shown to notably increase the energy storage capacity. [4,6,20] Moreover, freestanding biomass-derived have also been recently developed as potential candidates for flexible energy storage devices.…”
Section: Introductionmentioning
confidence: 99%
“…[2,17,18] Sevilla et al [13] reported N-doped carbons with surface areas of~2400 m 2 /g from hydrothermal carbonization and activation using microalgae as biomass precursor. The use of biomass-derived cellulose for producing porous carbons as electrodes for supercapacitor has also been reported giving excellent performance [19] and the incorporation of certain types heteroatoms into frameworks has shown to notably increase the energy storage capacity. [4,6,20] Moreover, freestanding biomass-derived have also been recently developed as potential candidates for flexible energy storage devices.…”
Section: Introductionmentioning
confidence: 99%
“…The recent advances in X‐ray computed tomography (CT) have allowed characterisation of the microstructure of many electrochemical devices such as lithium‐ion batteries, solid oxide fuel cells, polymer electrolyte fuel cells, supercapacitors, and, more recently, RFBs . The application of tomographic images in the study of porous media has the benefit of allowing numerical simulations to be conducted directly on the actual structures represented in the images, and therefore allowing prediction of the material's performance based on its microstructural properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have recorded high specific capacitance values with excellent cyclability and stability, owing to the use of innovative materials with optimized surface properties and porous texture [9][10][11]. However, there has been little work reported on the underlying factors that determine the relationship between structural form and electrochemical performance [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…These materials have been established as model systems and are easily tuned to achieve porous carbons of high specific surface areas that enhance the electrochemical performance of supercapacitors. Herein, cellulose of softwood pulp origin (Pinus Silvestris and Picea Abies, α-cellulose > 85 %) was activated using different KOH (Fisher Scientific, UK) loadings, as previously reported[12].Briefly, the cellulose samples (UPM-Kymmene Corporation, Finland) were prepared via blending with water to reach 1% consistency and 500 g m -2 . The samples were pressed at a pressure of 5000 lbs and temperature of 120 °C (Carver Inc., USA), then soaked in KOH solutions of different concentrations followed by carbonization at a heating ramp of 20 °Cmin -1 up to 850 °C for 1 h in 1 L min -1 nitrogen flow.…”
mentioning
confidence: 99%